Towards 2030 and more: Designing a sustainable Future - Costea, Carmen; Mihoreanu, Larisa; Stefanescu, Alexandru; Vasile, Adrian (Annals of Spiru Haret University. Economic Series, 2016)
Global development is not only a strategy, a practice, or a process. It is also a perception linked to mental constructs and desiderates a place to reinvent living and doing business. No matter the topic of it – social, economic, environmental, the single approach will never be enough. Changes in global development issue aggressive challenges of competition and uncertainty for market, society and individuals at a local level which impact more widely than expected described by complex systems science as the “butterfly flapping” effect influencing development in all its dimensions. The change comes along with opportunities, risks and challenges, which influence both life and work. In the present paper, we combat the myth of “no choice” policy and sustain the recovery of the fundamental values by exploring new approaches to the relationship between governments, markets, society and environment.